Latissimus Dorsi Tendon Transfer Vs. Superior Capsular Reconstruction for Treatment of Irreparable Massive Rotator Cuff Tears: A Retrospective Comparison Study with Short-Term Clinical Results. Issue 7 (29th July 2019) - Kadow, Tiffany; Garcia, Daniel; Minorini, Rebecca; Baratz, Mark; Delaney, Ruth; Lin, Albert
Objectives: Irreparable massive rotator cuff tears, particularly those that occur in younger patients, represent a particularly challenging clinical scenario with limited options. Treatments such as reverse total shoulder arthroplasty are typically not well indicated for this patient population. We compared two treatment methods, latissimus dorsi tendon transfer (LDTT) vs arthroscopic superior capsular reconstruction (SCR), to determine if one is superior to the other regarding improvement in range of motion (ROM) and patient reported outcomes (PROs). We hypothesize that both treatments would have similar outcomes regarding functional restoration and subjective outcomes. Methods: A retrospective cohort study assessed 43 patients with an irreparable posterosuperior rotator cuff tear after failed conservative or surgical treatment who underwent either LDTT (14 patients, 16 shoulders) or SCR (27 patients, 27 shoulders). Patients with a minimum of 6 month follow-up were included (mean follow up: 17.9 months, 14.9 months respectively). Changes in preoperative and postoperative forward flexion and external rotation were evaluated. Patient reported outcomes (PROs) including ASES, VAS, and SSV were assessed. T-test and Chi-Square statistical tests were performed. Results: The mean age at the time of surgery was 59.9yo vs 60yo for LDTT and SCR respectively (p=0.98). There were significantly more patients in the LDTT group that had undergone prior rotator cuff surgery (p<0.005) and significantly greater number of patients who had subscapularis tears which required repair in patients that underwent SCR (p<0.01). There was no difference in gender (p=0.75). Both cohorts demonstrated similar improvement in forward flexion with mean active forward flexion improving from 123° (90-160°) pre-operatively to 139° (80-180°) postoperatively in the LDTT group (p=0.157) and 85° (0-170°) preoperatively to 138° (40-175°) postoperatively in the SCR group (p =0.001). The average improvement in forward flexion was significantly greater in the SCR group with an improvement of 52° for SCR vs 14° for LDTT (p=0.035). External rotation improved in the LDTT cohort from 41° preoperatively (10-60°) to 62° (10-80°) (p=0.032) while external rotation stayed unchanged for the SCR cohort with 43° preoperatively (0-70°) to 44° (20-80°) postoperatively (p=0.868). The improvement in external rotation was significantly greater in the LDTT cohort with improvement of 19° vs 0.5° in the SCR group (p=0.011). There was no significant difference in reported ASES scores (LDTT: 65.6 vs SCR:70.9)(p=0.569), VAS (LDTT:1.78 vs SCR 2.26) (p=0.645), or SSV (LDTT:55 vs SCR:72.6) (p=0.087). Conclusion: LDTT and SCR both result in functional improvement of motion with SCR improving forward flexion to a greater extent and LDTT improving external rotation to a greater extent. Patient reported outcomes are similar between the two groups at short term follow up. Longer term outcomes are necessary before determining whether one treatment is optimal over the other as well as establishing the appropriate indications for each. Active Range of Motion Motion LDTT SCR p value Forward Flexion (degree) Preop 123.3° 85.19° Postop 139.38° 137.59° Mean Improvement 14° 52.41° p=0.035 External Rotation (degree) Preop 41.67° 43.4° Postop 61.54° 44.2° Mean Improvement 19.4° 0.8° p=0.011